One place two stories: The reproduction of the authentic in Beyoglu - Yalcin, Busra (Yildiz Technical Univ, Fac Architecture, 2023)
Authenticity, real or not, existing or not, constitutes an important element of strength for the urban environment. The perceived authentic identity of the place is transformed into economies of experience associated with consumer culture. Sometimes this can be in the form of transforming and protecting a historical building or neighborhood, sometimes supporting the development of cafes and shops, branding cultural identity, and sometimes presenting the place with new media channels. This problem plane, which constitutes the beginning of the study, aims to reveal the impact assessment process of an environment that is stuck between the existing place authenticity and the elements that are newly attributed to the place and that shape the authenticity in perceptions. Authenticity was first revealed in heritage conservation studies and was included in social science studies over time. Today, the concept is introduced into a new production and consumption process within the scope of urban area activities. While the authentic is sometimes defined as the memory that needs to be preserved with deeply emotional expressions, it is sometimes associated with a vulnerable imposition for consumption. In this cycle, the existing authenticity of the place cannot be revealed, and a new perceptual authenticity production is started. This study dealt with the spatial memory of Beyoglu and aimed to reveal the perceived and existing level of authenticity. The method step of the study was carried out in two stages as collecting data related to the problem and analyzing the data. Data were collected by snowball sampling method and document analysis technique. In the analysis step of the data, deductive content analysis was taken as reference. Category matrices were extracted, contexts and codes were revealed. The category matrix step, through Bennett's (2018) titles of screen, literary text, culture-art and project productions; context step, through Somers' (1994) public, ontological and meta narrative titles; the code step was created by the author through the concepts explained in theory and revealing the problem of the study. Codes; Goffman's (1959) onstage/backstage self discourse, MacCannell's (1976) false pattern discourse, Trancik's (1986) lost space discourse, Auge's (1995) non-places discourse, Boym's (2001) ) nostalgia discourse has been deepened by making use of Zukin's (2010) narratives such as cultural identity branding discourse. While the process carried out through document analysis and snowball sampling enables accurate determination of what, why, why, how and where to search and a reliable evaluation, categorizing the sources and coding their contents will reveal the changes and duality seen in the existing and perceived authenticity perspective. While losing the monumentality of Beyoglu's memory spaces that go beyond being a residence, the opera and dances introduced by the west, its stories, patisseries and people, an image object is produced over the nonexistent. The universal elite growth rhetoric, based on the economic power of the capital and the state, and the cultural power of the media and consumer tastes, has also surrounded Beyoglu. This situation is expressed by Guy Debord as contemporary capitalist modes of production produce a huge spectacle for societies. It has been an important finding for Beyoglu that the perceptual authenticity discourses, which symbolize the return to the past, also construct a new place memory culture and are shaped around the consumption potential. In summary, this study is important for an exploration to be made in a cultural space saturated with the spirit of self and place, to see where the cognitive dimension takes the subject in narratives and to embody what the space has lost in the social dimension with visual images. It can be said that the right solution can be found if the root experiences about Beyoglu can be revealed. Encountering the types of signs and narratives that will reveal these two meanings in Beyoglu is also an expression of the fact that the work is in the right qualitative production process. Based on the analyzes of the discourses and visual data collected throughout the study, the question of whether it is possible to prevent the falseness produced by this shift and updated experience environment of Beyoglu becomes very important. The study raises awareness by raising this question and provides this through a method trial.
Keywords: Beyoglu; existential authenticity; non-lieu; place crisis; perceived authenticity